(untitled) (Diametros, 2025)
The policy decision to recommend the vaccination of children against COVID was a controversial one - a controversy that Guibilini and colleagues characterize as stemming from expert disagreement. I argue that scientific dissent was not the primary issue here - rather, this is a problem of a persistent ambiguity concerning what standard needs to be met for the vaccination of children to be justified - which potential benefits should we take into account, and for whom? I trace the decision-making process in both the UK and the US to draw this out, and then consider some of the key ethical questions we need to consider when adopting a standard of justification.